Assessing educators’ personal characters on the usage of e-Learning in Wadi-Alhayat, higher education institution, Libya - Ali Taher, Abdussalam Mohamed; Dahari@Damiri, Rohaya (2016)
Enormous researches have emerged in the usage of E-learning.E-learning is so important to today’s educational system.The use of e-learning in educational institutions can ease the burdens associated with both teaching and learning processes, thereby improving the overall standard of education.Meanwhile, despite, its numerous benefits, its adoption in Wadi-Alhayat higher education institutions, Libya still remain unsatisfactory.Most educators in the institution have not seen the reason to adopt totally the service into the college educational system due to some issues.This has caused a lot of setback to efficient e-learning usage in the institution. Meanwhile, studies have identified that, educators’ personal characters is among numerous factors that can determine the use of e-learning among educators/instructors in higher learning institutions.Therefore, this study aims to assess this factor in relation to the use of e-learning among educators in Wadi-Alhayat higher education institution, Libya. This study used quantitative data where the data was collected through survey questionnaires distributed to educators’ in Wadi-Alhayat higher education institution, Libya.This type of data was quantified through the Likert scale, used in decoding the several variables that will be used to investigate the research issue and capture the respondents’ responses.The result from Pearson product-moment correlation revealed that relationship between educator’s personal character and the use of e-learning is an extremely low, non-significant relationship with a coefficient of correlation value (r) = 0.018.Therefore, finding shows that the hypothesized relationship between educator’s personal characters and usage of e-learning in Wadi-Alhayat higher education institution, Libya is statistically not related.